2015
DOI: 10.1038/srep16552
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TGF-β1-CD147 positive feedback loop in hepatic stellate cells promotes liver fibrosis

Abstract: Activation of hepatic stellate cells (HSCs) by transforming growth factor-β1 (TGF-β1) initiates HBV-associated fibrogenesis. The mechanism of TGF-β1 modulating HSC activation is not fully uncovered. We hypothesized a positive feedback signaling loop of TGF-β1-CD147 promoting liver fibrogenesis by activation of HSCs. Human HSC cell line LX-2 and spontaneous liver fibrosis model derived from HBV transgenic mice were used to evaluate the activation of molecules in the signaling loop. Wound healing and cell contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 38 publications
(52 reference statements)
2
69
0
Order By: Relevance
“…It has been recently reported that the TGF- β 1-activated SMAD4 complex may upregulate CD147 expression by directly interacting with a specific SBE in the CD147 promoter, thereby controlling HSC migration. 52 Here, we identified two SBEs in the miR-143 promoter and demonstrated that SMAD4 decreased miR-143 expression in pGCs by binding to SBE2 in its promoter. Interestingly, a recent study demonstrated that blockade of TGF- β signaling decreases the miR-143 level in smooth muscle cells.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…It has been recently reported that the TGF- β 1-activated SMAD4 complex may upregulate CD147 expression by directly interacting with a specific SBE in the CD147 promoter, thereby controlling HSC migration. 52 Here, we identified two SBEs in the miR-143 promoter and demonstrated that SMAD4 decreased miR-143 expression in pGCs by binding to SBE2 in its promoter. Interestingly, a recent study demonstrated that blockade of TGF- β signaling decreases the miR-143 level in smooth muscle cells.…”
Section: Discussionmentioning
confidence: 77%
“…49, 50 SMAD4 can complete extracellular TGF- β signal transmission by combining with SBEs of target promoters. 51, 52 TGF- β signaling has an important role during epithelial–mesenchymal transition. Specifically, binding of SMAD4 to the SBE within the promoter region of the CAR gene in breast epithelial cells 50 and the CDH2 gene in human pancreatic ductal epithelium 53 and non-small cell lung cancer cells 51 is necessary for TGF- β -stimulated transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Through autocrine and paracrine mechanisms, extracellular matrix components such as MMPs, fibrillary collagens and proteoglycans promote growth factor (mainly PDGF) and cytokine signaling. This signaling, particularly through the transforming growth factor-beta (TGF-β) and Wnt pathways, further activates HSCs, thus creating a positive, profibrotic feedback loop (Figure 1, Karsdal et al, 2015; Li et al, 2015). Ultimately, mechanotransduction- and growth factor-induced gene regulation by transcriptional regulators such as YAP and BRD4 mediate fibroproliferative disease and represents a unique target for pharmacological intervention for patients with liver fibrosis.…”
Section: Hepatocellular Stellate Cells Mediate Liver Fibrosismentioning
confidence: 99%
“…Numerous key profibrotic cytokines components of EMT have been identified, such as transforming growth factor-β (TGF-β), platelet-derived growth factor, and IGF-132. TGF-β, a multifunction cytokine, plays crucial roles in EMT program and fibrosis33343536. Arecoline could promote the transdifferentiation of human BMFs into myofibroblasts through activating integrin αvβ6/TGF-β1 signaling8.…”
Section: Discussionmentioning
confidence: 99%